Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Solve the system using substitution or elimination:

y = x^2 - 3x + 8

2x - y = -8

Please show and explain all steps, thank you for your help.


Sagot :

Answer:

x= 0, 5      y = 8, 18

Step-by-step explanation:

y = x^2 - 3x + 8 ..........eq 1

2x - y = -8 .............eq 2

from eq 2, lets make y the subject,

-y = - 8- 2x

y = 2x +8 ...........eq 3

using simultaneous method, using eq 1 and 3

2x+8 = x^2- 3x + 8

x^2 -5x=0

x(x-5) =0

x= 0, 5

if x = 0,

y = 2x+ 8 = 2(0)+8 = 8

if x = 5

y = 2(5) + 8 = 18